Bevacizumab increases the risk of anastomosis site leakage in metastatic colorectal cancer - Kim, Seijong; Shin, Jung Kyong; Park, Yoonah; Huh, Jung Wook; Kim, Hee Cheol; Yun, Seong Hyeon; Lee, Woo Yong; Cho, Yong Beom (Frontiers in Oncology, 2022)
Background: Bevacizumab is a humanized monoclonal antibody against vascular endothelial growth factor and is used in combination with first-line chemotherapy in the treatment of metastatic colorectal cancer. One of the side effects of bevacizumab is gastrointestinal perforation. This study was designed to identify the effect of bevacizumab in intestinal anastomosis site healing. Methods: From January 2010 to December 2020, patients diagnosed with stage IV colorectal cancer treated with palliative chemotherapy or chemoradiotherapy followed by radical surgery were retrospectively reviewed. Clinical signs or symptoms and computed tomography were tools used for diagnosing anastomosis site leakage. The patients were divided into two groups, the bevacizumab group (n = 136) and the non-bevacizumab group (n = 124). Results: Among the 260 patients 14 (5.4%) patients were diagnosed with anastomosis site leakage. In the bevacizumab group, 13 (9.6%) patients were diagnosed with anastomotic leakage. In the non-bevacizumab group, 1 (0.8%) patient was diagnosed with anastomotic leakage. Anastomosis site leakage was significantly higher in the bevacizumab treatment group (P < 0.001). In the bevacizumab group, period of drug discontinuation before surgery was factor associated with anastomosis site leakage in multivariable analysis (P = 0.031). Conclusion: Stage IV colorectal patients treated with bevacizumab before radical surgery for primary cancer should be carefully observed of anastomosis site leakage after surgery, and the period of drug discontinuation before surgery should be longer than 5 weeks to avoid anastomosis site leakage.